Analysis of Online Report Data of Death Cases in 2009–2013 in the Emergency Department of a General Hospital. (June 2014) - Gui, Chao; Chen, Huiqing; Zhou, Chunlian
Abstract Objective. To discuss the distribution of the epidemiological characteristics of the death cases in the emergency department such as age, gender, occupation, and the basic cause of death, and to provide the basis for the improvements in abilities to treat and cure critically ill emergency cases and the stipulation of preventive measures. Methods. Through the national cause-of-death registration reporting information system and according to the International Classification of Diseases (ICD-10), the 2009–2013 report data about the death cases in the emergency department of a general hospital were analyzed. Results. A total of 43.83% of the 2, 763 death cases of the emergency department were an elderly group of people ranging in ages from 60 to 79 and only 3.47% of the 2, 763 death cases were a young group of people of age less than or equal to 44; the male-female ratio was 1.18: 1; the basic causes of death were mainly diseases of the circulatory system (49.84%) and malignant neoplasms (22.26%); the occupations of the deceased patients were mainly production or transportation equipment operation or relevant workers (38.18%). Conclusion. According to the epidemiological characteristics of the death cases in the emergency department, a new strategy is devised to effectively prevent and cure diseases of the circulatory system among the age group at considerable risk and relevant occupational groups, and the mortality rate of emergency cases is decreased.